Removal of Dye from Wastewater Using a Novel Composite Film Incorporating Nanocellulose - Ismat Ara Eti; Marufa Khatun; Most. Afroza Khatun; Md. Owaleur Rahman; K. M. Anis-Ul-Haque; Md. Jahangir Alam (Advances in Polymer Technology)
Research shows that the composite material is used as an adsorbent to remove pollutants from wastewater. This work is aimed at producing a novel composite film comprising chitosan, polyvinyl alcohol, and cornstarch incorporating nanocellulose (CPCN). The composite film was prepared by a blending method wherein nanocellulose was extracted using a chemical method from banana bract. The prepared CPCN was characterized using Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) with EDX to understand their molecular interaction and surface morphology, respectively. The effect of parameters including pH, adsorbent dosage, initial dye concentration, and contact time on the adsorption of methylene blue (MB) dye was studied. The maximum adsorption was found to be up to 63.13 mg/g MB with a pH of 10, adsorbent dosage of 2 g, an initial concentration of 150 ppm, and contact time of 120 min at room temperature (25°C) indicating a moderate adsorption capacity of the CPCN. Comparing the Langmuir and Freundlich adsorption isotherm models, the former fitted well with MB dye adsorption data, implying that the models can be applied to uptake MB dye by CPCN. In the kinetic adsorption experiment, the adsorbed dye almost reached equilibrium at about 120 min for the CPCN and followed the pseudo-second-order kinetic model. Therefore, the CPCN can be used as a potential adsorbent in wastewater treatment.